The Contradictions of Public Service and Commercialisation in Mid-century South African Broadcasting: A Case Study of the Schoch Commission and Springbok Radio. Issue 2 (3rd April 2019) - Teer-Tomaselli, Ruth
Abstract : This study focuses on the 1950 introduction of the commercial radio station, Springbok Radio, into the South African Broadcasting Corporation, a Commonwealth inspired public service broadcaster (PSB) resulting from the Schoch Commission (1948). The paper argues that the introduction of Springbok Radio was prompted by the financial crisis faced by the Corporation; the broadcaster's attempt to broaden its appeal beyond elite audiences serviced by PSB; and the national imperative to centralise and control the broadcast sector by dominating it completely. Thus, the study examines the motifs of PSB versus commercialisation; high culture versus popular culture; and nationalism versus internationalisation.